Transformasi Sistem Politik Indonesia dalam Bayang-Bayang Sentralisasi Kekuasaan dan Politik Elit - HANI NURUL QHOTIMAH; INDAH RAHMA DANI; JASUAR ALIYYU KHATTA (Kampus Akademik Publiser, 2026)
Indonesia’s political system has undergone significant transformation, particularly since the transition from authoritarianism to democracy in the late 20th century. Despite the formal shift toward decentralization and democratic governance, patterns of power centralization and elite dominance remain influential in shaping political outcomes. This study aims to examine how these two dynamics centralization of authority and elite-driven politics interact within Indonesia’s evolving political system. Using a qualitative approach based on literature review and critical analysis, this research explores institutional developments, policy trends, and political behavior across different periods. The findings indicate that although decentralization policies were introduced to distribute power more evenly, in practice, political authority often reconsolidates at the national level through regulatory frameworks and elite networks. Furthermore, political elites continue to play a decisive role in controlling party structures, electoral processes, and policy directions, limiting broader public participation. These conditions create a paradox in which democratic procedures exist, but substantive democracy remains constrained. The study implies that strengthening institutional accountability, enhancing political inclusivity, and reducing oligarchic influence are essential steps toward achieving a more balanced and representative political system in Indonesia.